Assessment of social skills and university coexistence in Chilean higher education students (Revista Innova Educación, 2026)
Social skills and university coexistence are relevant components of the academic and social development of higher education students. The objective was to describe social skills and university coexistence among university students, with the aim of providing descriptive evidence to support the implementation of future formative actions. A quantitative study was conducted using a non-experimental, descriptive, cross-sectional design. The survey technique was employed, and data were collected through a structured Likert-scale questionnaire. It was administered to a sample of 20 students from the Bachelor’s Degree in Education at Miguel de Cervantes University (Chile), selected through purposive sampling, and analyzed using descriptive statistics. The results showed unfavorable perceptions in both variables. Regarding social skills, high percentages of disagreement and total disagreement were recorded, ranging from 75.5% to 83.5% for the effective communication dimension and from 70.5% to 85.0% for the social skills dimension, reflecting a negative appraisal of key aspects of socioemotional performance. Similarly, in university coexistence, the indicators across its dimensions showed high levels of disagreement, with percentages between 77.5% and 87.5%, revealing a generalized perception of weaknesses in the institutional climate. In conclusion, significant limitations in social skills and coexistence were identified, highlighting the need to strengthen formative actions aimed at improving the institutional climate.
Keywords: conflict resolution; culture of peace; higher education; interpersonal relationships; social skills